2x+5-6x=29

Simple and best practice solution for 2x+5-6x=29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+5-6x=29 equation:


Simplifying
2x + 5 + -6x = 29

Reorder the terms:
5 + 2x + -6x = 29

Combine like terms: 2x + -6x = -4x
5 + -4x = 29

Solving
5 + -4x = 29

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + -4x = 29 + -5

Combine like terms: 5 + -5 = 0
0 + -4x = 29 + -5
-4x = 29 + -5

Combine like terms: 29 + -5 = 24
-4x = 24

Divide each side by '-4'.
x = -6

Simplifying
x = -6

See similar equations:

| X+9+5x=21+2 | | 21/2=3d | | 12d+2-3d=5 | | 2x+x+(x+6)=54 | | x+5457+x=14165 | | 2(x+2)+2x=4(x+1) | | 32-(8-x)=36 | | 8x-5+2x=2(5x-5) | | 2a+3a=35 | | 2w^2+3w=77 | | 3a=5a | | 9x+6-4x=2x+1-16 | | 8(3x-1)=80 | | (1/4)x-(5/3)=-(1/2)+(19/4) | | 8x^3-18x^2-53x+105= | | 7c-cd=-20 | | 3(4-6x)=12 | | 6x-1(3x+8)=16 | | 2(x-6)=-2(x-4) | | 18x-11=6x | | 12x=13x-7 | | 61-p=14 | | q-17=23 | | 15=2x-4 | | -y^2(-8x^2-6xy-y^2)= | | 1.5x+7=22 | | 3n-8=16 | | 2y+3+y=1 | | -x+12-3x=28 | | 3/2+1=13 | | -1=9-.67X | | 8xy^4(2xy^2-7xy+9x)= |

Equations solver categories